Anti-Doping - Blank C; Leichtfried V; Fürhapter C; Müller D; Schobersberger W; 3 (Deutsche Zeitschrift für Sportmedizin, 2014)
Coaches are seen as strong influencing factors in the regulation of athletes behavior and attitudes, as well as being in a good position to transfer knowledge. Hence, they should be included in targeted education strategies in doping prevention. The current study aimed at evaluating the knowledge and attitudes of Western-Austrian coaches to outline possible associations between education and perceived and actual knowledge. A questionnaire divided into four main fields of interest: (a) perceived knowledge, (b) actual knowledge, (c) attitudes, and (d) coach behavior, was handed out to 135 sport teachers and coaches in Tyrol (response rate: 45.9%). Perceived knowledge was significantly lower than actual knowledge (72.2 and 87 out of 100, p<0.001). The score on attitudes was 86.8 (out of 100), outlining a positive anti-doping attitude. Coach behavior scored very moderately (48.7 out of 100). Coaches, confronted with the topic during primary education and subsequent training scored significantly higher in perceived knowledge compared to primary education only (77.3 vs 52.8, p<0.05). The goal of prevention strategies should be to increase actual knowledge by continuing training of the coaches, since only those who perceive themselves to be competent will actively address the topic and appear more trustworthy, thereby helping athletes develop and modify their own set of values.Key Words: Doping prevention, trainer, education, network